Method Evaluation In Measuring Brand Image And Brand Quality Using Rating, RANKING AND PICK - ANY APPROACH - ', Marhadi; Musfar, T. Firli; Noviasari, Henni (Jurnal Ekonomi, 2011)
This research attempt to test and compare three type of measurement technique in measuring brandimage and brand quality: rating, ranking, and pick any. The objective of this research is to test theconsumer consistency in their perception and attitude toward brand image and brand quality usingthree different measurement techniques. This research were replication Barnard & Ehrenberg (1990)and Driesener & Romaniuk (2006) which compare the compare three type of measurement technique inmeasuring brand image.There are three shampoo products acting as the research objects in this research: Clear, Dove, andPantene. Acting as the respondent for this research was 149 consumers who had use that three brandof shampoo. Data analysis were execute using mean score for rating technique, score order for rankingtechnique, and mode score for pick any technique.Results show that (a) measurement in brand image using rating, ranking, and pick any technique didnot show the same score and respondent have tendency to answer the questions inconsistently. (b)Measurement using rating and pick any techniques show consistent result.